Pendekatan Pedagogis untuk Memperkaya Keterampilan Berpikir Tingkat Tinggi Siswa pada Mata Pelajaran Ekonomi - Erika Feronika Br Simanungkalit; Ari Data; R.E.H.Riwu Manu; Agustina Butar- Butar; Fernando Saragih; Mises B.C Abineno (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The deficiency of higher-order thinking skills (HOTS) among students in Economics at Kupang City High School was the primary reason for the research. The objectives of this research are: 1) To determine the description and analysis of students' higher-order thinking skills in economics subject at Kupang City High Schools; 2) To find out the most appropriate pedagogical approach to enrich students' higher-order thinking skills in Economics subject at Kupang City high schools. The research method used is a descriptive research method through a quantitative approach. The population in the study is all high school students in Kupang City. The sampling method included non-probability sampling, specifically convenience sampling, and gathered a sample of 132 grade XI students from four senior high schools in Kupang City. The study's findings indicated that: 1) The higher-order thinking skills of grade XI senior high school students in Kupang City are comparatively low, with the lowest indicators being those of evaluating and creating; 2) The literature review revealed that the Social Constructivism and Constructivism educational approaches are effective methods for educators to implement in economics learning enhance students' higher-order thinking skills.